Building long-term marketing relationships: New perspectives on B2B financial services - E. Theron; N. S. Terblanche; C. Boshoff (South African Journal of Business Management, 2013)
The focus of this study was on the relevance of trust, satisfaction and commitment in maintaining a long-term relationship (intention to stay) with an exchange partner in a Business-to-Business (B2B) context in the financial services industry. The perceptions of 238 B2B clients of a leading South African provider of development capital were investigated. Since support could not be found for the existence of trust, commitment and satisfaction as distinct individual dimensions, this study provides empirical support for the amalgamation of some well-established individual dimensions into broader, more holistic dimensions as drivers of long-term relationship building.Contrary to expectations, B2B banking clients participating in this study appeared to regroup individual dimensions, in a heuristic fashion, to form new dimensions that influenced their attitude towards staying in a B2B relationship. As a result, building long-term marketing relationships seems to be a less complicated process than previously thought. Against this background, the primary contribution of the study is that it highlights the need for marketing practitioners to reconsider their current relationship-marketing strategies. As the findings of the study are inconsistent with conventional wisdom, they also challenge marketing academics to reconsider the theoretical foundations of relationship building in a B2B context.
Keywords: 650